Dendronized hyperbranched polymers containing isolation chromophores: design, synthesis and further enhancement of the comprehensive NLO performance1. Issue 31 (21st August 2015) - Tang, Runli; Chen, Hong; Zhou, Shengmin; Xiang, Wendi; Tang, Xi; Liu, Binwen; Dong, Yongqiang; Zeng, Huiyi; Li, Zhen
<x xml:space="preserve">Abstract</x> New dendronized hyperbranched polymers (DHPs) constructed by dendronized monomers, exhibit good comprehensive NLO performance, especially for thermostability.